A new mechanism for autophagy regulation of anti-tumor immune responses. Issue 12 (1st December 2020) - Thorburn, Andrew
ABSTRACT: In this commentary I discuss a recent paper that describes a new mechanism for how macroautophagy/autophagy regulates the immune response to cancer, and relate it to other recent studies in this area. These recent developments may allow more effective strategies to manipulate autophagy to improve cancer therapy.